Learning Management of Islamic Religious Education (PAI) Based on Multiple Intelligences at SMA IT Insan Mandiri Cibubur - Agus Syukur; Abuddin Nata; Dede Rosyada; Fadhilah Suralaga (International Journal of Islamic Thought and Humanities, 2023)
This research is entitled "Learning Management of Islamic Religious Education (PAI) Based on Multiple Intelligences at SMA IT Insan Mandiri Cibubur". The purpose of this research is to explain how the SMA IT Insan Mandiri Cibubur High School as an education provider institution applies the concept of "Multiple Intelligences" to makes a learning model based on "Multiple Intelligences". The writer deliberately took PAI learning as a sample to make it easier for writer in the research process and not to widen and focus too much. Because in essence this study aims to find out a comprehensive model of the concept of learning based on multiple intelligences. This research is a type of qualitative research with a phenomenological approach. The conclusions of this study stated: That the implementation management of the "Multiple Intelligences" based learning concept that implemented by SMA IT Insan Mandiri Cibubur includes the learning planning process, learning implementation and assessment of learning outcomes. In planning learning, teacher use a database of students' multiple intelligences research (MIR) results, this is to make it easier for teachers to prepare lesson plans (RPP), and than teacher can choose a variety of strategies and learning methods, which are adjusted to the learning style and intelligence tendencies of students. Then in the implementation of learning, the teacher implements what has been prepared in the lesson plan (RPP) by implementstion with attractive learning and fun learning with the aim of sparking the various potentials of the students and using the “quantum teaching method” and implementation of project based qur’an (PBQ). The last process is the assessment of learning outcomes,  by using authentic assessment, its named a balanced and objective assessment in each domain, both cognitive, affective and psychomotor.